Assessing the Feasibility and Implications of Implementing One Nation One Election in India - Aarif Mohd Waza (International Journal of Advanced Technology and Social Sciences, 2023)
This research focuses on evaluating the feasibility and implications of implementing the One Nation One Election initiative in India. The study examines the advantages and challenges of conducting simultaneous elections at all levels of government, including its potential impact on democratic principles, political parties, and voter behaviour. The research also analyses the legal and constitutional aspects of this initiative and explores the practical considerations involved in its implementation, such as coordinating election schedules and deploying resources effectively. The findings of this study provide valuable insights into the potential benefits and drawbacks of One Nation One Election, and offer recommendations for policymakers and stakeholders to consider when evaluating its feasibility